An enriched maternal environment and stereotypies of sows differentially affect the neuro-epigenome of brain regions related to emotionality in their piglets - Patricia Tatemoto; Fábio Pértille; Thiago Bernardino; Ricardo Zanella; Carlos Guerrero-Bosagna; Adroaldo José Zanella (Epigenetics, 2023)
Epigenetic mechanisms are important modulators of neurodevelopmental outcomes in the offspring of animals challenged during pregnancy. Pregnant sows living in a confined environment are challenged with stress and lack of stimulation which may result in the expression of stereotypies (repetitive behaviours without an apparent function). Little attention has been devoted to the postnatal effects of maternal stereotypies in the offspring. We investigated how the environment and stereotypies of pregnant sows affected the neuro-epigenome of their piglets. We focused on the amygdala, frontal cortex, and hippocampus, brain regions related to emotionality, learning, memory, and stress response. Differentially methylated regions (DMRs) were investigated in these brain regions of male piglets born from sows kept in an enriched vs a barren environment. Within the latter group of piglets, we compared the brain methylomes of piglets born from sows expressing stereotypies vs sows not expressing stereotypies. DMRs emerged in each comparison. While the epigenome of the hippocampus and frontal cortex of piglets is mainly affected by the maternal environment, the epigenome of the amygdala is mainly affected by maternal stereotypies. The molecular pathways and mechanisms triggered in the brains of piglets by maternal environment or stereotypies are different, which is reflected on the differential gene function associated to the DMRs found in each piglets’ brain region . The present study is the first to investigate the neuro-epigenomic effects of maternal enrichment in pigs’ offspring and the first to investigate the neuro-epigenomic effects of maternal stereotypies in the offspring of a mammal.